Actors of the Political Socialization of the Youth - A. M. Sosnovskaya; S. A. Levina (Управленческое консультирование, 2024)
The formation of political identity of contemporary Russian youth is a dynamic socialization process involving constant communication with various actors and reassessment of norms and beliefs in political and cultural media discourse. Using the methods of actor-network theory, we can better understand how individual groups, accounts construct political identity through cultural narratives and practices by means of their affordances. Such properties of actors build trust in them in the case of discursive coincidences and common frames of self-identity within the network. By examining the practices of actors and the effects of their affordances in political socialization, we can understand how these processes shape the collective beliefs and the practices of young people that follow.The purpose of the article is to identify the sources of political socialization of student youth as actors by examining the trust mechanisms that contribute to successive processes of socialization formation.Methods of survey, focus groups, text analysis, actor-network theory methods, and Python, Gephi, and Google Excel programs were applied to map and represent the results.The study analyzed essays, surveys, and interviews (300 students in total) in order to qualitatively identify actors that influence the political socialization of young people. These actors include official cultural policies, family, school, media and social networks, church, society, political leaders and bloggers. The research allowed us to identify the most stable cognitive, affective and practical components of these actors’ discourses, emphasizing the special significance of cultural and historical facts in the formation of political identity.The process of political socialization begins in childhood and continues in the following stages of personal development, always intertwined with one or another social reflection, forming a coherent picture of the world. Young people trust information supported by facts and consistent with their worldview; young people are influenced by parents, official sources and bloggers. In the political sphere, young people are interested in political leaders, elections, the work of government bodies, and the influence of politics on areas of life such as culture and ecology.The analysis conducted in the optics of ANT has revealed the mechanisms of how student youth are influenced by various actors and how this influence shapes their political beliefs and behavior. The study emphasizes the importance of constant communication for the formation of youth political identity through the influence of various actors in media discourse.